KELEBIHAN MEMPELAJARI AL QUR’AN (Studi Relevansi dengan Teori Belajar) - Ridlwan, Burhanuddin (Al Tadib : Jurnal Ilmu Pendidikan, 2014)
Understanding learning is a process of philosophical activity to achieve changes in knowledge, habits, and attitudes. The change was achieved by conscious, functional, positive, active, focused, sustained, and covers all aspects of the behavior of the cognitive, psychomotor, and affective. and there are several ways to read and memorize the Qur'an as a form of learning that could achieve change. While learning achievement is the result of changes in the ability of definitive, psychomotor, and affective it. That is obtained in a frail and period, measured by the standardized test. There are some several factors that influenced student achievement, namely: from external factors such as environmental and instrumental, form factor in studying the physiology and the psychology excess. The advantage of al Quran is,: first, the cognitive side: it is the mastery of Arabic vocabulary, rule of grammar in verse, the knowledge contained in the verse and understanding of the value of literature in verse, second: the Psychomotor: Skilled in planning reading the Qur'an (recitation), also makhraj (the entry and exit of the letters in the oral) and achievement recitation of the verses of al Qur'an. Thirdly, affective side: like clean and pure, sincere, increased faith, sobriety, and self-control with the morals of the Qur'an.Keywords: Learning, Learning Achievement, Learning the Qur'an.